How medium-sized tourism enterprises responding business environment changes for its sustainability - Chairunnisa, Rina; Febriansyah, Hary (Journal of Business and Management, 2020)
Abstract. The sustainability issues faced by Medium-sized Tourism Enterprises challenge the ability of entrepreneurs to not falter and continue to survive. The tourism sector whose situation fluctuates depending on how business or market performance and external conditions require entrepreneurs toadapt and make policies to be sensitive to change. In this research, this observation was carried out in Bandung with a questionnaire involving 16 respondents and semi-structure in-depth interview involving four informants. The background problem of this study is the impact of actions taken in change management towards sustainability of Medium-sized Tourism Enterprises in Bandung. The research is aimed at knowing the responses to changes in the business environment, the needs to be developed to implement change management strategies, and the scope of Medium-sized Tourism Enterprises in Bandung in making changes for its sustainability. The Star Model will be the framework for effective strategy execution. How the organization can effectively align the components with each other makes a huge difference in achieving an impact. Furthermore, the author will look at the business forms and types of changes made based on the analysis of the Star Model elements of the framework to link to sustainability by Medium-sized Tourism Enterprises in Bandung.Keywords: Medium-sized Enterprises, Tourism, Change Management, Sustainability.